Assessment of water consumption during Ramadan intermittent fasting: Result from Indonesian cross-sectional study - Sunardi, Diana; Chandra, Dian Novita; Medise, Bernie Endyarni; Friska, Dewi; Manikam, Nurul Ratna Mutu; Lestari, Wiji; Insani, Putri Novia Choiri; Ayusari, Amelya Augusthina; Mayasari, Diana; Saftarina, Fitria; Sari, Dina Keumala; Ulvie, Yuliana Noor Setiawati (Frontiers in Nutrition, 2022)
During Ramadan fasting, people are likely to consume water and beverages lower than recommendation due to the limited time. However, it is necessary to achieve the recommended daily water intake, to maintain the hydration status as well as the productivity during the. Unfortunately, there is a lack of data on drinking patterns during Ramadan. This study aimed to investigate water and beverages intake and drinking pattern to help achieving water requirement during Ramadan among Indonesian adults. This study was a cross-sectional study conducted during Ramadan period from April to May 2021 (Ramadan 1442 Hijri). We used self-administered questionnaire of drinking habit during Ramadan and utilized 7-day fluid record (Liq.In 7) to assess water and beverages intake among participants who were managed through online procedure. There were 380 participants from five universities across Indonesia who completed the questionnaire accordingly and then analyzed. The result shows that total water and beverages intake during Ramadan among participants was below the recommendation (1670 (1326 – 2034) ml/day). Among the type of beverages, water is the highest level consumption (1262 (983 – 1666) ml/day) then followed by sugar-sweetened beverages (200 (91 – 350) ml/day). We found a significant difference in water and beverages consumption between time of iftar (474 (375 – 590) ml/day), night time (574 (414 – 810) ml/day), and suhoor (560 (423 – 711) ml/day). From this study, we found that during Ramadan, the most commonly drinking pattern is 2-4-2, but drinking pattern of 4-2-2 glasses (sequence of 4 glasses at iftar, 2 glasses at night time, 2 glasses at suhoor) had a significantly higher chance to adhere with the recommendation of fluid intake compared to other patterns. Therefore, based on this research on water and beverages intake, it is necessary and important to make improvements among Indonesian adults during Ramadan, the drinking pattern of 4-2-2 glasses may help to achieve the recommended daily water consumption.